Ethics and economics: growing opportunities for joint research. - Hosmer, LaRue Tone; Chen, Feng (Business Ethics Quarterly, 2001)
A group of economists has recently begun addressing questions at the intersection of ethics and economics. They are preparing new definitions of individual choice that combine self-interest and other-interest, new processes of interpersonal exchange that result in cooperation rather than conflict, and new measures of social well-being that include rights as well as outcomes. This article surveys that work, and suggests areas where conceptual inputs from business ethicists are clearly needed, and where multiple opportunities for interactive research are obviously present. Reprinted by permission of the publisher.